The Interaction of TRAF6 With Neuroplastin Promotes Spinogenesis During Early Neuronal Development - Vemula, Sampath Kumar; Malci, Ayse; Junge, Lennart; Lehmann, Anne-Christin; Rama, Ramya; Hradsky, Johannes; Matute, Ricardo A.; Weber, André; Prigge, Matthias; Naumann, Michael; Kreutz, Michael R.; Seidenbecher, Constanze I.; et al. (Frontiers in Cell and Developmental Biology, 2020)
Correct brain wiring depends on reliable synapse formation. Nevertheless, signaling codes promoting synaptogenesis are not fully understood. Here, we report a spinogenic mechanism that operates during neuronal development and is based on the interaction of tumor necrosis factor receptor-associated factor 6 (TRAF6) with the synaptic cell adhesion molecule neuroplastin. The interaction between these proteins was predicted in silico and verified by co-immunoprecipitation in extracts from rat brain and co-transfected HEK cells. Binding assays show physical interaction between neuroplastin’s C-terminus and the TRAF-C domain of TRAF6 with a Kd value of 88 μM. As the two proteins co-localize in primordial dendritic protrusions, we used young cultures of rat and mouse as well as neuroplastin-deficient mouse neurons and showed with mutagenesis, knock-down, and pharmacological blockade that TRAF6 is required by neuroplastin to promote early spinogenesis during in vitro days 6-9, but not later. Time-framed TRAF6 blockade during days 6–9 reduced mEPSC amplitude, number of postsynaptic sites, synapse density and neuronal activity as neurons mature. Our data unravel a new molecular liaison that may emerge during a specific window of the neuronal development to determine excitatory synapse density in the rodent brain.